Analisis karakteristik sosial dan ekonomi usaha pedagang kaki lima di Kecamatan Telanaipura Kota Jambi (studi kasus pedagang nasi goreng) - Alpin Hardiansyah; Selamet Rahmadi Rahmadi; Parmadi Parmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2020)
This study aims to determine and analyze: 1). Social characteristics of fried rice street vendors in Telanaipura District, Jambi City, and 2). Economic characteristics of street vendors of fried rice in Telanaipura District, Jambi City. The data analysis method used is the descriptive quantitative analysis method. The results of the study were obtained: 1). The social conditions of fried rice traders in Telanaipura Sub-district are: the average age is the productive age of 42.78 years, the highest level of education and the most are SMA / SMK, all fried rice traders are male, the marital status is the most married. , the average length of effort is 8.39 years, the average number of dependents is 5 people, most fried rice traders have their own homes, most of the original areas of fried rice traders come from Central Java Province, the average length of hours fried rice traders work 9 hours per day and the average fried rice trader has his own business and place of business. 2). The social conditions of fried rice traders in Telanaipura Subdistrict are: venture capital for most fried rice traders is their own, the average amount of initial business capital is Rp. 6,233,333, the average length of day of selling in one month is 28 days, the average price of one serving of fried rice is Rp. 13,270.77. Keywords: Fried rice traders, Social characteristics, Economic characteristics